Volume Change and Liver Parenchymal Signal Intensity in Gd-EOB-DTPA-Enhanced Magnetic Resonance Imaging after Portal Vein Embolization prior to Hepatectomy. (11th September 2014) - Akiba, Ayako; Murata, Satoru; Mine, Takahiko; Onozawa, Shiro; Sekine, Tetsuro; Amano, Yasuo; Kawano, Youichi; Uchida, Eiji; Kumita, Shin-ichiro
Abstract : Purpose. To investigate the liver volume change and the potential of early evaluation by contrast-enhanced magnetic resonance imaging (MRI) using gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid (Gd-EOB-DTPA) after portal vein embolization (PVE). Materials and Methods. Retrospective evaluations of computed tomography (CT) volumetry of total liver and nonembolized areas were performed before and 3 weeks after PVE in 37 cases. The percentage of future liver remnant (%FLR) and the change ratio of %FLR (%FLR ratio) were calculated. Prospective evaluation of signal intensities (SIs) was performed to estimate the role of Gd-EOB-DTPA-enhanced MRI as a predictor of hypertrophy in 16 cases. The SI contrast between embolized and nonembolized areas was calculated 1 week after PVE. The change in SI contrast before and after PVE (SI ratio) was also calculated in 11 cases. Results. %FLR ratio significantly increased, and SI ratio significantly decreased (both P < 0.01 ). There were significant negative correlations between %FLR and SI contrast and between %FLR and SI ratio (both P < 0.01 ). Conclusion. Hypertrophy in the nonembolized area after PVE was indicated by CT volumetry, and measurement of SI contrast and SI ratio in Gd-EOB-DTPA-enhanced MRI early after PVE may be useful to predict the potential for hepatic hypertrophy.